Strategi Pembelajaran Bahasa Inggris Melalui English Club dalam Meningkatkan Motivasi Peserta Didik di MI Darussalam Candi Sidoarjo - Sutrisno, Tri; El-Yunusi, Muhammad Yusron Maulana (Indo-MathEdu Intellectuals Journal, 2024)
The aim of this research is to determine the effectiveness of the English club in learning English, which makes it easier to understand and also overcomes students' self-confidence. The research method used is qualitative with a descriptive approach with data collection techniques through observation and interviews. Data analysis techniques collected come from primary and secondary data. Primary data comes from observation, namely observing directly the activities of teachers and students and then conducting interviews to dig up information about the roles, strategies and obstacles faced in English Club activities. Secondary data includes documentation collected in the form of photos, videos and media for learning activities. The informants in this research were teachers and students at MI Darussalam Sugihwaras Candi Sidoarjo. The research results show that learning English through English Club activities is able to increase students' motivation in overcoming feelings of lack of self-confidence, fear and embarrassment because the learning provides an exciting and comfortable atmosphere. Presentation of interesting and effective material combined with games and singing. Overall, the learning process in overcoming lack of self-confidence and fear by participating in English Club activities has an effective impact on students.